Embodied and hybrid pedagogies: - I. Nell (Acta Theologica)
This article aims to explore ecumenical tours as one example of glocal learning and as a case in point. Making use of the central concepts of embodied and hybrid pedagogies as hermeneutical lenses, the main research question is: Does the exposure of students through ecumenical tours, as part of the Master of Divinity programme, foster embodied and hybrid pedagogies, and if so, in what ways? Factors at play in ecumenical exposure include the content of the programme, the diversity of the student population, as well as the reflective and participatory practices of teaching, learning, and assessing in lived faith contexts. The article especially emphasises a one-day pilgrimage among the lived faith practices.